Progress and Challenges of Renewable Energy Transition in Indonesia’s Energy Mix Towards Net Zero Emissions - Syabriyana, Maliya (Fakultas Teknik Universitas Samudra, 2024)
Indonesia's journey toward a zero-emission future is a complex and multifaceted endeavor, driven by its commitment to sustainable energy practices and reducing its carbon footprint. In 2021, the Indonesian government revised and submitted its Nationally Determined Contributions (NDC), reinforcing its commitment to the Paris Agreement's goal of achieving net zero emissions by 2060 or earlier. As part of this effort, the government has set ambitious targets for the energy mix, aiming for 23% new and renewable energy by 2025 and 31% by 2050. On the path to reaching these targets, several significant strides have been made in policy development and the establishment of energy transition facilities. This article examines the progress made in the renewable energy sector, focusing on policy initiatives, progress of integration of renewable energy into the national energy grid, and its challenge. Despite these advancements, Indonesia faces substantial challenges in achieving its zero-emission goals. In conclusion, while Indonesia has made commendable progress in its renewable energy transition, realizing a zero-emission energy mix will require sustained efforts and strategic planning.